Direct Detection and Characterization of Shiga Toxigenic Escherichia coli by Multiplex PCR for stx(1), stx(2), eae, ehxA, and saa - Paton, Adrienne W. (American Society for Microbiology, 2002)
We recently described a novel megaplasmid-encoded adhesin produced by certain Shiga toxigenic Escherichia coli (STEC) strains that lack the locus for enterocyte effacement (LEE) pathogenicity island. This adhesin, designated Saa (STEC autoagglutinating adhesin), may be a marker for a subset of LEE-negative STEC strains capable of causing severe gastrointestinal and systemic diseases in humans. In this study, we developed a pentavalent PCR assay for the detection of saa as well as other proven and putative STEC virulence genes (stx(1), stx(2), eae, and ehxA). The five primer pairs used in the assay do not interfere with each other and generate amplification products of 119, 180, 255, 384, and 534 bp.